Research on Basic Theory and Key Technology of Cognitive Radio Network - Ping Zhang; Jianwu Li; Zhiyong Feng; Qixun Zhang (Dianxin kexue)
Cognitive radio network（CRN）is a cognitive process of network，which makes planning，decision and response for network state through learning and analysis of the network environment.CRN is one of the effective ways to solve the limited network capacity，and to satisfy the national strategic demand on the frequency spectrum efficient-utilization and the integration of heterogeneous networks.As the key technology of 5G，CRN indicates the direction for the future development of wireless communication network.The system architecture for cognitive radio networks，the basic theory research，the key technologies of implementation were introduced，and the demonstration platform of CRN was presented.